Ulnar Collateral Ligament Injury in Gymnasts: An Analysis of Return to Competition Rates and Patient Outcomes. Issue 7 (30th July 2021) - Rao, Somnath; Jack, Robert; Willier, Donald; Cohen, Steven; Dodson, Christopher; Ciccotti, Michael; D'Amore, Taylor
Objectives: While results following ulnar collateral ligament (UCL) injury in baseball players has been well documented, results following UCL injury in gymnasts are not well documented. As such, the purpose of this study was to report the operative and non-operative outcomes of UCL injury in gymnasts. Methods: Gymnasts who underwent UCL injury treatment whether non-operative or operative at a single institution were evaluated at a minimum of 2 years post-operatively. Patients were assessed with Kerlan-Jobe Orthopaedic Clinic Shoulder and Elbow Score (KJOC), Mayo Elbow Performance Score (MEPS), Andrews-Timmerman (A-T) Elbow score, Quick Disabilities of the Arm, Shoulder and Hand (qDASH) score and a custom return to play survey. Results: There were 11 patients who met inclusion criteria and complete follow-up was available in 9 patients. Overall, 6 patients were treated operatively (4 UCL reconstructions (UCLR) and 2 UCL repairs) and 3 patients were treated non-operatively. One UCLR was performed after 2 months of failed non-operative management. All patients were female with a mean age of 16.1 (range, 12-20) and mean BMI of 24.46 (range 19.2-34.1) at time of surgery or initial visit. Average follow-up was 4.04 years. Overall, 66.7% of operative versus 100% of non-operative were able to RTP at an average of 7.5 and 7 months, respectively. One re-injury was reported in the non-operative group, which was a re-dislocation of the elbow unrelated to gymnastics and was ultimately treated non-operatively. The mean KJOC, MEPS, A-T and qDASH scores for the operative group were 70.0 (range, 48.5-89), 97.5 (range, 95-100), 90.8 (range, 75-100) and 24.6 (range, 22.7-29.5), respectively. The mean scores for the non-operative group were 75.9 (range, 61-91.2), 71.7 (range, 65-75), 71.7 (range, 55-80) and 34.1 (range, 22.7-40.9), respectively. Conclusions: Both operative and non-operative treatments can be offered as successful treatment options for UCL injuries in gymnasts. Further investigation is needed to determine the optimal management of UCL injuries in gymnasts.